Spring rape supply with basic nutrients depending on fertilizers rates - Гарбар, Л. А. (Scientific Progress & Innovations, 2012)
Research results on dynamic of macronutrients content in spring rape plants during vegetation depending on different fertilizers rates stated in this article. Research shows that basic (NPK) macronutrients more intensively accumulates at the beginning of vegetation and than reutilized moving from vegetative to generative organs thus provides normal growth and development of plants on further vegetation.